PENGARUH INTEREST RATE DAN FINANCIAL DISTRESS TERHADAP STOCK RETURN - Sri Wahyuni Nur; Andi Tenri Uleng Akal; Nurlaela Nurlaela (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this research is to know the effect of interest rate, and financial distress of stock return on manufacturing company listed on the Indonesia Stock Exchange from 2019-2021. The sampling method used in this research is purposive sampling with 47 manufacturing company. Data used for this study is obtained from financial statement for the year ended December 31st during 2019-2021. Analysis tool that will be used to analyze the hypothesis with multiple linier regression model is software IBM SPSS (Statistical Product and Service Solutions) version 23.0 for Windows. The result for this research showed that interest rate have positive and significant effect on stock return, while financial distress has positive and not significant effect on stock return.